Community structure and substrate characteristic of marine worm (polychaete) in mangrove coastal water Peniti, West Kalimantan - JUNARDI JUNARDI; ELVI RUSMIYANTO PANCANING WARDOYO (Society for Indonesian Biodiversity, 2008)
The research was conducted in the mangrove coastal water in Peniti, West Kalimantan. Peniti mangrove coastal water has high species richness and diversity of polychaetes. We have collected 43 species of polychaetes. Most of them are deposit feeders with Dodecaceria sp. and Sternaspis scutata showed highest abundance among all species. The substrate characteristic was muddy-clay and the high carbonorganic content.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: Polychaete, substrate characteristic, community structure, mangrove.